Hubungan perilaku ibu tentang pemberian makanan pendamping ASI (MP-ASI) dengan tumbuh kembang bayi 6-12 bulan - Manalu, Media Sarilestari; Simatupang, Melva (Colostrum Jurnal Kebidanan, 2021)
Stunting is a chronic nutritional problem in toddlers characterized by a shorter height compared to other children of their age. In 2018, according to data from the World Health Organization, Indonesia ranked 4th in the world by contributing 9 million (23.6%) children with stunting out of 159 million Indonesian children. Complementary foods are breast milk that is no longer able to meet the nutritional needs of babies because of the increasing nutritional needs of babies and babies need additional food that accompanies breast milk as their main food. This study aims to determine the correlation between mother's behavior and complementary feeding  with the growth and development of babies aged 6-12 months in the work area of Medan Sunggal community Health Center in 2020. The research method used was analytical with a cross sectional approach. The sample was all mothers who have babies aged 6-12 months as many as 55 respondents. The majority of mothers knowledge about complementary feeding with good knowledge of 42 people (76.4%) and 13 people (23.6) in poor category. The majority of mothers' attitudes about complementary feeding have positive traits totaling of 39 people (70.9%) and negative categories totaling of 16 people (29.1%). The majority of mothers' actions regarding complementary feeding have positive characteristics, amounting to 40 people (72.7%) of respondents and 15 people (27.3) in the unfavorable category. The results of the bivariate analysis obtained p value = 0.000 <0.05 which means that there was significant correlation between knowledge, attitudes and actions of mothers regarding.